2022
DOI: 10.1111/cts.13318
|View full text |Cite
|
Sign up to set email alerts
|

An association study of ABCG2 rs2231142 on the concentrations of allopurinol and its metabolites

Abstract: ABCG2 is a gene that codes for the human breast cancer resistance protein (BCRP). It is established that rs2231142 G>T, a single nucleotide polymorphism of the ABCG2 gene, is associated with gout and poor response to allopurinol, a uric acid‐lowering agent used to treat this condition. It has also been suggested that oxypurinol, the primary active metabolite of allopurinol, is a substrate of the BCRP. We thus hypothesized that carrying the rs2231142 variant would be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…By extension, these findings suggest that carriers of the T allele, taking the same dose as those without the T allele, would be expected to have increased urate-lowering response, rather than the reduced response noted in other work. 3,[20][21][22][23][24] By contrast, some studies 8,21,25 have not found a relationship between ABCG2 genotype and oxypurinol PKs. The results of our study suggest that the reported association between ABCG2 genotype and allopurinol treatment response is not the result of altered oxypurinol PKs and may reflect alterations in urate disposition.…”
Section: Discussionmentioning
confidence: 95%
“…By extension, these findings suggest that carriers of the T allele, taking the same dose as those without the T allele, would be expected to have increased urate-lowering response, rather than the reduced response noted in other work. 3,[20][21][22][23][24] By contrast, some studies 8,21,25 have not found a relationship between ABCG2 genotype and oxypurinol PKs. The results of our study suggest that the reported association between ABCG2 genotype and allopurinol treatment response is not the result of altered oxypurinol PKs and may reflect alterations in urate disposition.…”
Section: Discussionmentioning
confidence: 95%
“…The selection of individuals was previously reported 15,16 . Succinctly, the two studies included self‐reported “White” males and females aged ≥18 years.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the ABCG2 gene polymorphisms on the pharmacokinetics of multiple drugs has been demonstrated [ 345 , 346 ]. Upregulated ABCG2 expression leads to a reduction in the drug plasma concentrations [ 347 , 348 , 349 ], while the downregulation and/or reduced-of-function variations tend to produce higher drug levels [ 345 , 350 , 351 ].…”
Section: Pharmacogenomics Of Transportmentioning
confidence: 99%
“…The T carriers of Q141K were linked to high risk of gout and reduced response to gout treatment by allopurinol [ 359 , 360 ]. However, recent studies have found no association between rs2231142 and oxypurinol, or allopurinol riboside plasma concentrations [ 346 , 361 ]. In other studies, the T carriers not only produced high concentrations of other BCRP substrates such as rosuvastatin and imatinib, but also generated a greater therapeutic effect of the drugs [ 345 , 346 , 362 , 363 , 364 , 365 ].…”
Section: Pharmacogenomics Of Transportmentioning
confidence: 99%
See 1 more Smart Citation